THE DEVELOPMENT OF PERSONNEL INDIVIDUAL MOTIVATION SYSTEMS WITH REGARD TO THEIR SOCIAL AND PSYCHOLOGICAL COMPETENCE - Svetlana A. Ledneva (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The current social and economic situation in this country and in the world is characterized by instability and numerous challenges that advance higher and higher requirements to personal and professional qualities of specialists. The article analyzes correlation between motives of work and elements of social and psychological competence of personality as a basis for designing effective individual motivation systems in the organization. The author discusses possibilities to use individual motivation profile of the employee and the level of cognitive, value and behavioral elements of the structure of social and psychological competence in order to stimulate employee’s labour behavior desirable for the organization.